The Impact of Rainfall on Production of Bajra in Solapur District (International Journal of Food and Nutritional Sciences, 2022)
This study examines the impact of rainfall on Bajra (Pearl Millet) production in Solapur district of Maharashtra, India. Being a drought-prone region with highly variable rainfall, Solapur‟s agricultural productivity is directly influenced by climatic conditions. Using secondary data from 2004–05 to 2013–14 and applying Pearson‟s Coefficient of Correlation, the study reveals a moderate positive correlation (+0.543) between rainfall and Bajra production. However, rainfall alone explains only 29.48% of the total variation in yield, indicating that other factors such as soil type, temperature, irrigation facilities, and farmers‟ practices significantly affect productivity. The findings highlight the need for improved irrigation infrastructure, adoption of high-yielding seed varieties, and modern agricultural practices to stabilize Bajra production in drought-prone areas.